If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(2/3)*y-((1/6)*y)+4 = 18 // - 18
(2/3)*y-((1/6)*y)-18+4 = 0
(2/3)*y+(-1/6)*y-18+4 = 0
1/2*y-14 = 0 // + 14
1/2*y = 14 // : 1/2
y = 14/1/2
y = 28
y = 28
| 3-4n=-12-7n | | 5n/10=25 | | 13=3w-5 | | 6b+3=7+2b | | 5/6k=7/18 | | x/14-5x+2/49=3x-4/7 | | 8(8-7a)=176 | | 1/n=3/9 | | 10(x+1)=10 | | 9=13-x+5x | | 28/35=40/j | | 4(-1)=-12-(-9) | | t/6=96/16 | | 5m^2+17m-66=0 | | 3(1)=1-2(2) | | 3(2x)-2=2(3x+9) | | 3u-9=18 | | 3(not-2)-19=5+2(n+5) | | 2(1)=0-2 | | 15/3.9 | | -6.6z-2.8+6.7z=28 | | 45/x=15/3 | | m+17=2m | | 59+3y-27=13y-10-4y | | 2a-1=a+4 | | 6(x+4)=2(3x+5)+14 | | 0.5x+14.2=x-1.45 | | 2/3n=10 | | 0.6x+14.2=x-1.45 | | (x/5)+12=8 | | 2p-7p=-15 | | -10-5x=-10 |